Anal abscess microbiology as an anal fistula predictor - Victoria Eugenia Dowling Enez (Journal of Coloproctology, 2020)
In order to determine the microbiology of anal abscess as a predictor of anal fistulas in patients who attended the external consultation of the Coloproctology unit of the Dr. Antonio María Pineda University Central Hospital, a prospective, descriptive, longitudinal study was conducted from September 2018 to July 2019. In this study, the population consisted of patients with a diagnosis of anal abscess, without associated comorbidities or contraindications for surgery, who agreed to be included in the study. A non-probabilistic, intentional sample consisting of 42 patients was determined. An appointment-based study protocol was applied by outpatient for patients who met the inclusion criteria applied, to perform due medical history through anamnesis, physical examination and culture taking of suppuration from the anal abscess to subsequently establish medical and surgical behavior thereof. The results were expressed in absolute numbers and percentages, a prevalence of ischiorectal abscesses was observed, followed by deep post-anal space abscesses. Anaerobic bacteria were isolated in 100% of the sample. In all fistulized patients, E. Coli was isolated as a predominant germ. Resumo: Um estudo prospectivo, descritivo e longitudinal foi realizado de setembro de 2018 a Julho 2019 para determinar a microbiologia do abscesso anal como preditivo de fístulas anais em pacientes que compareceram à consulta externa da unidade de Coloproctologia do Hospital Central da Universidade Dr. Antonio María Pineda. Neste estudo, a população foi composta por pacientes com diagnóstico de abscesso anal, sem comorbidades ou contraindicações associadas à cirurgia, que concordaram em participar do estudo. Uma amostra intencional não probabilística, composta por 42 pacientes foi determinada. Um protocolo de estudo com base na consulta em regime ambulatorial foi aplicado aos pacientes que atenderam os critérios de inclusão estabelecidos, para realizar a anamnese, o exame físico e a devida cultura da supuração do abscesso anal para posteriormente estabelecer o comportamento médico e cirúrgico. Os resultados foram expressos em números absolutos e porcentagens, observando-se a prevalência de abscessos isquiorretais, seguidos por abscessos profundos no espaço pós-anal. Bactérias anaeróbias foram isoladas em 100% das amostras. Em todos os pacientes com fístulas, E. Coli foi isolada como um germe predominante.